Role of Non-Verbal Communication In Education - Okon, John J. (Mediterranean Journal of Social Sciences, 2011)
Educators rely on verbal communication as a central tool for providing students with valuable information for academicdevelopment. Our daily nonverbal behaviors reveal who we are and impact how we relate to other people. Nonverbalcommunication has implication for the teacher as well as the learner. It is often said that one can always recognize a languageteacher by their use of gesture in normal conversation. Feldman (1990) asserts that research regarding the use of non-verbalcues in education demonstrates that educators often send messages regarding their expectations via non-verbal cues such asfacial expressions and overall body language. These nonverbal cues, according to Feldman, can have a notable impact onoutcomes for student response and behavior. With the realization that non-verbal communication can play such an importantrole in the process of education, there is a direct impetus to further examine this issue. Using this as a foundation forinvestigation, the current research considers the issue of non-verbal communication between students and teachers in thecontext of mitigating and managing conflict. By understanding these cues, educators can work to improve outcomes whenconflict arises with a student in the classroom.